The Influence Of Product Quality, Service Quality And Sales Promotion On Increasing Sales According To An Islamic Economic Perspective (Case Study: UMKM Bakery in Bengkalis - Bantan District, Bengkalis Regency) - Sri Kurnialis; Mahyarni Mahyarni; Trian Zulhadi (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
This research aims to analyze the influence of products, service quality and sales promotions on increasing sales according to an Islamic economic perspective. This research uses quantitative methods with multiple regression analysis. A sample of 96 respondents used an accidental sampling technique taken from UMKM Bakeries located in Bengkalis-Bantan District, Bengkalis Regency. Results show that the product quality label variable has an effect on increasing sales. The service quality variable has a positive and significant effect on increasing sales. The sales promotion variable has a positive and significant effect on increasing sales. This research seeks to reveal the influence of products, service quality and sales promotions on increasing sales according to an Islamic economic perspective. This research provides important insights for MSME Bakeries located in Bengkalis-Bantan District, Bengkalis Regency, to understand the factors that influence increased sales. By paying attention to product quality, service quality and sales promotions, you can optimize the sales strategy and product development of UMKM Bakery to meet the needs and preferences of consumers in Bengkalis City.